2022
DOI: 10.1039/d2sm00420h
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of a tunable photothermal actuator via in situ oxidative polymerization of polydopamine nanoparticles in hydrogel bilayers

Abstract: Photothermally triggered actuation enables the remote and local control of a material. The complex actuation can be achieved by controlling the photothermal efficiency of the material, which is crucial for...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Some polymers that can alter its shape under specific light without the precise shape programming posttreatment, such as the reversible swelling-deswelling of poly(n-isopropylacrylamide) (PNIPA) in water under temperature changes. 79 This actuating process only requires the intrinsic physical nature of polymers rather F I G U R E 3 (A) Schematic illustration of the preparation of anisotropic hydrogel and the actuation behavior. (B) SEM images of anisotropic structure.…”
Section: Photothermal Actuationmentioning
confidence: 99%
“…Some polymers that can alter its shape under specific light without the precise shape programming posttreatment, such as the reversible swelling-deswelling of poly(n-isopropylacrylamide) (PNIPA) in water under temperature changes. 79 This actuating process only requires the intrinsic physical nature of polymers rather F I G U R E 3 (A) Schematic illustration of the preparation of anisotropic hydrogel and the actuation behavior. (B) SEM images of anisotropic structure.…”
Section: Photothermal Actuationmentioning
confidence: 99%
“…It was demonstrated that adjusting the concentration of Ca 2+ can tune the mechanical properties of alginate hydrogels over a wide range, enabling them to be applied in different scenarios. [93][94] Unlike polysaccharides, protein-based hydrogels, such as collagen, tend to gel spontaneously without induction from the external environment. Collagen also contains many cell-signaling domains present in the extracellular matrix in vivo that can directly promote wound healing.…”
Section: Natural Hydrogelmentioning
confidence: 99%
“…It was demonstrated that adjusting the concentration of Ca 2+ can tune the mechanical properties of alginate hydrogels over a wide range, enabling them to be applied in different scenarios. [ 93–94 ]…”
Section: Photothermal Hydrogelsmentioning
confidence: 99%
“…in response to external stimuli, showing great promise in developing smart materials. Based on the interesting structure and excellent performance, such as remarkable flexibility, softness, superior absorption capacity in their swollen state, nontoxicity, biocompatibility, biodegradability and tunable mechanical properties [1,11] , polymer hydrogels have been used as superabsorbent materials [12] , for industrial wastewater treatment [13] , to build various of intelligent apparatus and actuators [14][15][16][17] , to control drugs delivery and release [18,19] , to engineer artificial muscles and tissue [20][21][22][23] . Hydrogels characterized by recognizing and responding specifc analytes such as human metabolites [24] , heavy metal ions [3,25,26] , anionic species [4,27] , etc.…”
mentioning
confidence: 99%